PEMANFAATAN POWER POINT UNTUK MENINGKATKAN PENGUASAAN KONSEP INTERAKSI ANTAR NEGARA ASIA DAN NEGARA LAINNYA DI SMP NEGERI 9 BULUKUMBA - Dg Mapata (LPPM Universitas Muhammadiyah Bulukumba, 2021)
The purpose of this class action research is to improve the quality of students learning processes and outcomes through the implementation of learning strategies that focus on student activities using power point-based media. This research was conducted at SMP Negeri 9 Bulukumba. The subject of the study was an IXa grade student. The research was conducted in the odd semester of the 2018/2019 school year for three months, namely August to October 2019. The problem discussed in this study is the application of learning strategies that use power point-based media to improve the mastery of the concept of Interaction Between Asian countries and Other Countries as a result of learning ips students in class IXa SMP Negeri 9 Bulukumba. The research data was netted using (1) observation sheets of teachers ability to implement learning strategies that focus on student activities by using power point-based media, and (2) test learning outcomes. This type of data is quantitative data so that the analysis is done using descriptive statistical analysis techniques. The results of the data analysis showed that the implementation of learning strategies that focus on student activities by using power point-based media can improve the mastery of the concept of Interaction Between Asian and Other Countries in students of grade IXa SMP Negeri 9 Bulukumba.